Profile of Scientific Creativity Based on Project Based Learning of Physics Education Undergraduate Students: Preliminary research - Sumo, Maimon; Jatmiko, Budi; Supardi, Zainul Arifin Imam (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
This research aims to describe the profile of scientific creativity abilities of undergraduate students in the basic physics 1 course through the application of the Project-based Learning model. The sample in this research was 50 undergraduate physics education students at Madura Islamic University taking introductory physics courses. The data obtained was analyzed quantitatively and then described. The students' scientific creativity profile was obtained by administering a scientific creativity test and a student response questionnaire using the implementation of Project Based Learning. The data was analyzed using a score calculation formula, the results were categorized into very high, high, medium and low category. After obtaining the scoring, the data is interpreted in percentage form. Meanwhile, student response questionnaire were measured using Likert scale and then interpreted in percentage form. The research results showed that 83% of students' scientific creativity was still classified as low, while 17% of students' scientific creativity was classified as moderate. With details of the creative personal character profile for each indicator of scientific creativity as follows: 1) Scientific Phenomena 52.5%, 2) Scientific Knowledge 15%, 3) Scientific Problem solving 13.75%, 4) Creative thinking ability 20.4%, 5) advanced scientific product design 12.7 %, and 6) Technical product 8.7%. The results of the student response questionnaire showed that the majority of students experienced difficulty in write their initial knowledge about physics, difficulty in solving problems and answering questions based on the scientific phenomena presented.